Allogeneic cord blood regulatory T cells decrease dsDNA antibody and improve albuminuria in systemic lupus erythematosus - Lyu, Mi-Ae; Tang, Ximing; Khoury, Joseph D.; Raso, Maria Gabriela; Huang, Meixian; Zeng, Ke; Nishimoto, Mitsutaka; Ma, Hongbing; Sadeghi, Tara; Flowers, Christopher R.; Parmar, Simrit (Frontiers in Immunology, 2023)
Lupus nephritis (LN) constitutes the most severe organ manifestations of systemic lupus erythematosus (SLE), where pathogenic T cells have been identified to play an essential role in ‘helping’ B cells to make autoantibodies and produce inflammatory cytokines that drive kidney injury in SLE. Regulatory T cells (Tregs), responsible for decreasing inflammation, are defective and decreased in SLE and have been associated with disease progression. We hypothesize that treatment with allogeneic, healthy Tregs derived from umbilical cord blood (UCB) may arrest such an inflammatory process and protect kidney damage. We show, UCB-Tregs are able to suppress pathogenic SLE cells, accompanied by secretion of the suppressor cytokine, IL-10 and a corresponding decrease in several inflammatory cytokines including IFN-, IP-10, TNF-, IL-6, IL-17A, and sCD40L in a time-dependent manner. In a xenogeneic SLE model, injecting single or multiple doses of UCB-Tregs led to decrease in CD8+ T effector cells in different organs and decrease in systemic inflammatory cytokines in vivo. Improvement in skin inflammation and loss of hair was also observed in UCB-Treg recipients. Immunohistochemistry of renal tissue showed resolution of CD3+, CD8+, CD20+ and Ki67+ SLE-PBMC infiltration in UCB-Treg recipients. UCB-Tregs decreased plasma anti-double stranded DNA IgG antibody levels and improved albuminuria. We conclude that UCB-Tregs can decrease inflammatory burden in SLE, reduce auto-antibody production and resolve end organ damage especially, improve kidney function. Adoptive therapy with UCB-Tregs should be explored for treatment of lupus nephritis in the clinical setting.